SAAS parallel task scheduling based on cloud service flow load algorithm - Zhu, Jian; Li, Qian; Ying, Shi (Computer communications, 2022)
In cloud platform applications, the user’s goal is to obtain high-quality application services, while the service provider’s goal is to obtain revenue by performing the tasks submitted by the user. The platform built by the service provider’s application resources needs to improve the mapping between service requests and resources to achieve higher value. Through the current situation of resource management in the cloud environment, it is found that many task scheduling and resource allocation algorithms are still affected by factors such as the diversity, dynamics, and multiple constraints of resources and tasks. This paper focuses on Software as a Service (SaaS) applications’ task scheduling and resource configuration in a dynamic and uncertain cloud environment. It is a challenging online scheduling problem to automatically and intelligently allocate user task requests that continually reach SaaS applications to appropriate resources for execution. To this end, a real-time task scheduling method based on deep reinforcement learning is proposed, which automatically and intelligently allocates user task requests that continually reach SaaS applications to appropriate resources for execution. In this way, the limited virtual machine resources rented by SaaS providers can be used in a balanced and efficient manner. In the experiment, by comparing with other five task scheduling algorithms, it is proved that the algorithm proposed in this paper not only improves the execution efficiency of better deploying workflow in IaaS public cloud, but also makes the resources provided by SaaS are used in a balanced and efficient manner.